APLIKASI TEORI HUMANISTIK DALAM INTERAKSI DOSEN-AMAHASISWA DI PERGURUAN TINGGI - Nursanjaya Nursanjaya (Negotium: Jurnal Ilmu Administrasi Bisnis, 2020)
Humanistic theory emphasizes equal development of student’s cognitive and affective aspects. In a humanistic teaching, students have to study and record the progress the have made by themselves. Although the theory has not yet been implemented in our college setting, it can actually be applied in the interaction between the lecturer and students in the classroom. The lecturer gives the freedom and responsibility to the students to study and functions as a fasilitator, who facilities the students to freely express their feeling and emotions.